Wacana Filosofis Komponen Pendidikan Islam - Fathullah ; Moch. Yunus (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2021)
Abstract Studying the philosophy of Islamic education means entering the arena of basic, systematic, logical and comprehensive thinking about education, which is not only motivated by Islamic religious knowledge, but requires us to study other relevant sciences. In carrying out philosophical thinking, in essence, it is an effort to mobilize all human psychological potentials such as thoughts, intelligence, will, feelings, memories, and observations of the five senses about the symptoms of life, especially humans and the natural surroundings as God's creation. The whole thought process is based on theories from various disciplines and with deep and wide experiences about the problems of life and reality in the universe and in itself. Keywords: Componen, Piloshopy, Islamic Education